2003
DOI: 10.1016/s0021-9290(02)00417-7
|View full text |Cite
|
Sign up to set email alerts
|

Optical determination of anisotropic material properties of bovine articular cartilage in compression

Abstract: The precise nature of the material symmetry of articular cartilage in compression remains to be elucidated. The primary objective of this study was to determine the equilibrium compressive Young's moduli and Poisson's ratios of bovine cartilage along multiple directions (parallel and perpendicular to the split line direction, and normal to the articular surface) by loading small cubic specimens (0.9×0.9×0.8 mm, n=15) in unconfined compression, with the expectation that the material symmetry of cartilage could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
116
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 36 publications
24
116
1
Order By: Relevance
“…Important aspects and results of these analyses were that: (1) 2D cartilage strains were computed at equilibrium for both confined [29] and unconfined test protocols [23,36], (2) strains in the thickness direction varied as a function of depth, and (3) strains perpendicular to the thickness direction were either generally zero [23,29] or at least an order of magnitude smaller than strains in the thickness direction [34]. Based on these strain fields, it was possible to compute estimates for equilibrium moduli [28,33]. Also, all strain components changed nonlinearly with increasing load [34].…”
Section: Introductionmentioning
confidence: 99%
“…Important aspects and results of these analyses were that: (1) 2D cartilage strains were computed at equilibrium for both confined [29] and unconfined test protocols [23,36], (2) strains in the thickness direction varied as a function of depth, and (3) strains perpendicular to the thickness direction were either generally zero [23,29] or at least an order of magnitude smaller than strains in the thickness direction [34]. Based on these strain fields, it was possible to compute estimates for equilibrium moduli [28,33]. Also, all strain components changed nonlinearly with increasing load [34].…”
Section: Introductionmentioning
confidence: 99%
“…First, we require that the first-order constants {λ 11 , λ 22 , λ 33 } be continuous across the surfaces of discontinuity. The rationale for this requirement is that previous analyses suggested that material stability is difficult to ensure if the first-order constants jump, because eight stiffness matrices must be positive-definite (see, Klisch et al 2004;Wang et al 2003). Second, we neglect the secondorder terms associated with λ and μ [see Eqs.…”
Section: Bimodular Second-order Orthotropic Materialsmentioning
confidence: 99%
“…The proteoglycans are negatively charged molecules that mainly resist compressive loads (Basser et al 1998;Lai et al 1991) while the collagen net work primarily resists tensile and shear loads (Mow and Ratcliffe 1997;Venn and Maroudas 1977). Due to this molecular structure, articular cartilage typically exhibits a mechanical response with marked anisotropy and tension-compression asymmetry (Akizuki et al 1986;Laasanen et al 2003;Soltz and Ateshian 2000;Wang et al 2003;Woo et al 1976Woo et al , 1979, and likely experiences finite, multi-dimensional strains due to typical in vitro and in vivo loads. Although MRI mea surements of in situ and in vivo joints have predicted that cartilage is subject to average strains of less than 10% under physiologic loading conditions (Eckstein et al 2000;Herberhold et al 1999), local strains may be much higher due to nonhomogeneous mechanical properties that depend on both anatomic location and depth from the articular surface (Schinagl et al 1997;Wang et al 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations